Chaos Bandwidth Enhancement of Fabry-Pérot Laser Diode With Dual-Mode Continuous-Wave Optical Injection - Hong Han; Ming Jiang Zhang; Shore, K. Alan (IEEE journal of quantum electronics, 2019)
We show numerically that dual-mode continues wave optical injection into a Fabry-Pérot laser diode subject to optical feedback generates a chaos bandwidth, which is four to six times that without optical injection. As a comparison, it is shown that single-mode optical injection can increase the chaos bandwidth threefold with careful choice of detuning. Furthermore, any combination of dual-mode injection will enhance the chaos bandwidth and especially for strong injection and over relatively large positive detuning ranges. Even, when the bias current of the Fabry-Pérot laser diode is relatively low, the bandwidth of chaos can reach 35 GHz after dual-mode optical injection, which is six times than that of without optical injection. The enhanced bandwidth with dual-beam optical injection is in accordance with our previous experiments [25]. The present simulations provide detailed guidance on the choice of experimentally accessible parameters to generate chaotic signals with enhanced bandwidth by using single or dual-beam optical injection into a Fabry-Pérot laser diode with optical feedback.